Group of women with two $100,000 Y.W.C.A. pennants - Unknown:::Creator::::::::::::
Fundraising women (left-to-right) Mattie More, May Parks, unidentified, unidentified, Bessie Collins, Mrs J. W. The woman on the far left and the fourth woman from the left are holding $100,000 Y.W.C.A. pennants. On June 2, 1914, the Y.W.C.A. of San Jose started their 10 day building campaign with a goal to raise $100,000. They succeeded and raised $105,310 which they used to build a three story building on Second and San Antonio streets in San Jose, California. From: Smith, p. 25-29.